Maternal Characteristics and the Effects of Early and Late-onset Types of Preeclampsia on Maternal and Perinatal Complications - Damayanti, Sintia; Sulistyowati, Sri; Probandari, Ari Natalia (Indonesian Journal of Medicine, 2019)
Background: Preeclampsia is still the main cause of morbidity and mortality not only for mothers but also for fetal. The concept of early and late-onset preeclampsia is a more modern concept, and it is stated that these two entities have different etiologies and must be considered as different forms of the disease. This study aims to analyzing differences in maternal characteristics (age, number of parity, history of hypertension and diabetes mellitus) and laboratory results (platelet, ewitz, Lactic Acid Dehydrogenase/LDH) and to analyzing differences in maternal complications (maternal death, eclampsia, impending eclampsia, pulmonary edema, (hemolysis, elevated liver enzyme levels, and low platelet levels/HELLP syndrome) and perinatal complications (perinatal death, Intrauterine Growth Restriction/IUGR, fetal hypoxia and fetal distress) between early and late-onset preeclampsia. This study aimed to investigate the maternal characteristics and the effects of early and late-onset types of preeclampsia on maternal and perinatal complications.Subjects and Method: This was a retrospective cohort study. The study was carried out at Dr. Moewardi Hospital, Surakarta, from January 1, 2016, to December 31, 2017. A total of 548 pregnant mothers with preeclampsia was selected for this study. The dependent variable was the incidence of preeclampsia. The independent variables were age, parity, hypertension, diabetes Mellitus, platelets, LDH, and proteinuria. The data were obtained from the medical record and analyzed by a multiple linear regression.Results: The number of patients with early-onset (162) was less than late-onset (386). More patients have multiparity in early and late-onset. In early-onset preeclampsia, thrombocytopenia and LDH increase tend to be present, and ewitz >+1. Early-onset preeclampsia tends to result in more maternal and perinatal complications.Conclusion: The incidence of early-onset is less than late-onset, but early-onset provides worse complications for both maternal and perinatal.Keywords: Early-onset preeclampsia, late-onset preeclampsia, characteristics, maternal and perinatal complicationsCorrespondence: Sintia Damayanti. Department of Obstetrics and Gynecology, Dr. Moewardi Hospital/ Faculty of Medicine, Universitas Sebelas Maret, Surakarta, Central Java, Indonesia. Email: sintiadamayan84@yahoo.co.id. Mobile: 082220020829.Indonesian Journal of Medicine (2019), 4(4): 329-338https://doi.org/10.26911/theijmed.2019.04.04.05